(untitled) (Bangladesh Journal of Medicine, 2020)
Introduction :In Bangladesh, the first confirmed case of COVID1 9 was detectedon 8th March’2020, almost 3 months after the initial outbreak in late December’ 2019 in Wuhan, China.The number of affected cases and deaths both have become exponential during this global pandemic. Clinical data on COVID 19 in Bangladesh is still lacking. The objective of our study was to evaluate clinico-demograhic Profile, treatment Outline & clinical outcome within a defined period among COVID-19 Bangladeshi Patients. Methods: We conducted a retrospective multicenter descriptive study on epidemiological & clinical profile along with treatment outcomes of 236 Rt-PCR confirmed patients of COVID 19 from COVID dedicated units of 3 hospitals- Dhaka Medical College Hospital ( DMCH)(n-87), Kuwait Bangladesh Moitry Hospital ( KBMH)(n-50),Popular Medical College Hospital ( PMCH)(n-99) during the period of May to July 2020 with a pre-determined case record form. Results: Among the total 236 patients, highest percentage of patients (26%) belonged to 50-59 years age range, however it was found that no age was immune.Regarding gender distribution, two-third patients were male (65%) & one-third patients were female (35%).The predominant symptoms of our enrolled patients were fever (89%), cough (85%) & dyspnea (76%) ,fatigue (23%), chest pain (23%)& anosmia (19.5%), followed by gastro-intestinal symptoms. Almost half of the patients had been suffering from Hypertension (48%) and Diabetes (47%) Regarding treatment, 100% patients received tromboprophylaxis with low molecular weight Heparin (LMWH)& around 2/3 patients received steroid in different forms following treatment protocol of our national guideline. 20% patients required ICU support & death rate was 4.7%. Around two-third patients could be discharged in < 10 days’ time. Conclusion: Covid-19 in Bangladesh is presented in adult male with fever, cough and dyspnoea predominantly with occasional lack of taste and smell. Supportive care was effective with predominantly good outcome Bangladesh J Medicine July 2020; 31(2) : 52-57